Survey of submediterranean leguminous species in Serbian flora - Mrfat-Vukelic S.; Kojic M.; Lugic Z.; Ostojic S. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
This paper presents submediterranean leguminous species which appear in natural meadow and pasture, phytocenoses of Serbia. There have been included genera Trifolium, Medicago, Onobrychis and Lotus. A great number of species (33,3 per cent) has an excellent, very good and good quality, which makes their collection and the process of selection possible. It was found that, out of the total number of species of genus Trifolium, 40 per cent belong to the submediterranean group of floral elements, 45,5 per cent from genus Medicago, and 83,3 per cent from genus Onobrychis, also belong to it, while there are no species from genus Lotus.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)